Life cycle environmental assessment of retaining walls in unsaturated soils. (June 2022) - Speranza, Gianluca; Ferrari, Alessio; Lassalle, Pyrène Larrey
Abstract: Retaining structures above groundwater level support soils that are usually in a state of partial saturation and subject to the actions of atmospheric agents. The current design approach considers the possible extremes of soil conditions – either totally dry or totally saturated – but it neglects matric suction's contribution to soil shear strength. This work aims to describe how unsaturated-soil mechanics of can positively influence the sustainability of retaining structures through a holistic, multidisciplinary, geotechnical, and environmental analysis. The geotechnical analysis allows to estimate the lateral earth pressure of a geostructure in both unsaturated and extreme soil conditions (dry or saturated), which will directly influence the geometrical dimensions of the geostructure. Next, the environmental analysis is performed with the standardized and globally applied Life Cycle Assessment (LCA) tool, in order to quantify the potential environmental impacts of the retaining structure according to both a life cycle and a multi-criteria perspective. First, an LCA model is built for a cantilever retaining wall according to two design approaches: (a) an unsaturated design approach (UDA), i.e. when unsaturated soils' principles are considered in the design procedure, and (b) a conventional design approach (CDA), i.e. if soil is considered dry or saturated. Three different types of retained soil (i.e. fine-grained soil, volcanic ash, and coarse-grained soil) are considered. Then, the associated environmental impacts on climate change, human health, ecosystems and resources are calculated for the two design approaches. Their comparison allows to quantify the potential reductions in environmental damages provided by the adoption of unsaturated-soil mechanics. The presented case study shows a high potential reduction in environmental impacts for retaining walls interacting with fine-grained soils (silt), lower potential environmental benefits with volcanic ash (clayey–silty sand), but no environmental gain for interaction with a coarse-grained soil (sand) compared to a conventional design approach considering extreme soil conditions. Highlights: Lateral earth pressure of unsaturated soils considering seepages for three soils. Life cycle assessment model for a cantilevered retaining wall. Environmental performance: conventional design approach vs unsaturated design approach.